Evaluation of stress distribution on an endodontically treated maxillary central tooth with lesion restored with different crown materials: A finite element analysis - Ömer Kirmali; Gülsah Icen; H. Kursat Celik; Allan E.W. Rennie (Heliyon, 2024)
Objectives: The biomechanical response of teeth with periapical lesions that have been restored using various substructure materials, as well as the stress mapping in the alveolar bone, has not been thoroughly described. In this context, the objective of this study is to investigate the structural stress distributions on root canal-treated maxillary right central incisors with lesions restored using different crown materials under linear static loading conditions through finite element analysis (FEA). Methods: In the study, five FEA models were utilised to represent healthy teeth and teeth restored with different substructure materials: (A) a healthy tooth, (B) a lesioned, root canal-treated, composite-filled tooth, (C) a lesioned, fiber-posted, zirconia-based crown, (D) a tooth with lesions, a fiber post, and Ni–Cr infrastructure crown, (E) a tooth with a lesion, a fiber post, and an IPS E-max infrastructure crown. A force of 100 N was applied at an angle of 45° to the long axis of the tooth from 2 mm cervical to the incisal line on the palatal surface. Deformation behaviour and maximum equivalent stress distributions on the tooth sub-components, including the bony structure for each model, were simulated. Results: Differences were observed in the stress distributions of the models. The maximum stress values of the models representing the restorations with different infrastructures varied, and the highest value was obtained in the model of the E-max crown (Model E: 136.050 MPa). The minimum stress magnitudes were obtained from Model B the composite-filled tooth (80.39 MPa); however, it was observed that the equivalent stresses in all the models showed a similar distribution for all components with varying magnitudes. In periapical lesion areas, low stresses were observed. In all models, the cervicobuccal collar region of the teeth had dense equivalent stresses. Conclusion: Different restorative treatment methods applied to root canal-treated teeth with periapical lesions can impact the stress in the alveolar bone and the biomechanical response of the tooth. Relatively high stress values in the cortical bone at the cervical line of the tooth have been observed to decrease towards the apical region. This observation may suggest a potential healing effect by reducing pressure in the periapical lesion area. Clinical significance: Composite resin restorations can be considered the first-choice treatment option for the restoration of root canal-treated teeth with lesions. In crown restorations, it would be advantageous to prefer zirconia or metal-supported prostheses in terms of biomechanics.